Gluten-Free Foods Cooked in Shared Fryers With Wheat: A Pilot Study Assessing Gluten Cross Contact - Thompson, Tricia; Lyons, Trisha Bury; Keller, Amy; Jaffe, Nancee; Emerson-Mason, Luke (Frontiers in Nutrition, 2021)
Introduction: Consumers with celiac disease are dissuaded from eating fried foods cooked in shared fryers with wheat-containing foods at restaurants based on presumed gluten exposure. The purpose of the present study is to assess gluten levels of fries free of gluten-containing ingredients cooked in shared fryers with wheat. Methods: 20 orders of fries were purchased from 10 different restaurants. Restaurants confirmed that fries and oil were free of gluten-containing ingredients. All restaurants confirmed that their fryers were used to cook wheat-containing foods. Fries were sent to Bia Diagnostics and tested in 1-gram duplicates using the R7001 sandwich R5 ELISA and the R7021 competitive R5 ELISA. A microwave control also was run. Results: The sandwich ELISA found gluten in 9/20 fry orders (7 to > 84 ppm). The competitive ELISA found gluten in 3/20 fry orders (14 to > 283 ppm). In the microwave control (60-ppm gluten mixture of wheat flour and canola oil) , the unheated mixture tested at a mean level of 64 ppm gluten using the sandwich ELISA and 137 ppm gluten using the competitive ELISA. The mixture heated to 190°C tested at a mean level of 55 ppm gluten using the sandwich ELISA and < 10 ppm and 16 ppm gluten using the competitive ELISA. Discussion: Based on test results, 25% of fry orders would not be considered gluten-free. Summary: Gluten cross contact may occur when gluten-free foods are cooked in shared fryers with wheat. ELISAs may underperform when analyzing for gluten that has been heated.